The Effects of Korean Celebrities on Millennial & Gen Z Purchase Intention In Indonesia’s Beauty Industry - Adam Jordy; Mega A. Yulianti; Nadya Chloe; Reynaldi Romy; Sartika Sari Hasibuan (Indonesian Business Review, 2023)
This research aims to find the effect of using Korean celebrities towards purchase intention using several criteria in Indonesia’s beauty industry. The data were collected by distributing online surveys to the public with age criteria of Gen-Z and Millenials in Indonesia who like or adore Korean celebrities. Thus, Convenience sampling method was applied. Questionnaires acquired and recorded using a five point comparative scale. Exploratory factor and multiple regression analysis were used in analyzing criteria on customers’ purchase intention. Three aspects affecting purchase intention were identified, namely, connectedness towards celebrities, attitude towards celebrities, and celebrities cause-fit. Results from regression analysis proved that the connectedness and celebrities cause-fit have significant positive effects on customers’ purchase intention. Results from this research intended to help marketers when planning on using Korean celebrities as their brand ambassador. Marketers can acquire meaningful perception of factors that have significant impact in influencing customers’ purchase intention.